Au nanorod assembly for sensitive SERS detection of airway inflammatory factors in sputum - Yang, An-qi; Zheng, Wentong; Chen, Xiaoyang; Wang, Jiayin; Zhou, Shuang; Gao, Hongzhi (Frontiers in Bioengineering and Biotechnology, 2023)
In this paper, we demonstrate a surface-enhanced Raman spectroscopy (SERS) biosensor based on the self-assembly of gold nanorods (AuNRs) for the specific detection of airway inflammatory factors in diluted sputum. The AuNR surface was modified with an antibody that was able to specifically recognize an airway inflammatory factor, interleukin-5 (IL-5), so that a end-to-end self-assembly system could be obtained, resulting in an order of magnitude amplification of the Raman signal and greatly improved sensitivity. Meanwhile, the outer layer of the biosensor was coated with silicon dioxide, which improved the stability of the system and facilitated its future applications. When the detected concentration was in the range of 0.1–50 pg/mL, the SERS signal generated by the sensor showed a good linear relationship with the IL-5 concentration. Moreover, it had satisfactory performance in diluted sputum and clinical subjects with asthma, which could achieve sensitive detection of the airway inflammatory factor IL-5. Overall, the developed biosensor based on the SERS effect exhibited the advantages of rapid and sensitive detecting performance, which is suitable for monitoring airway inflammatory factors in sputum.